Nano-zerovalent copper as a Fenton-like catalyst for the degradation of ciprofloxacin in aqueous solution. (October 2020) - Shah, Noor S.; Khan, Javed Ali; Sayed, Murtaza; Iqbal, Jibran; Khan, Zia Ul Haq; Muhammad, Nawshad; Polychronopoulou, Kyriaki; Hussain, Sajjad; Imran, Muhammad; Murtaza, Behzad; Usman, Muhammad; Ismail, Issam; et al.
Graphical abstract: Highlights: Zerovalent copper materials were prepared and used for degradation of ciprofloxacin. Use of H2 O2 with copper nanoparticles facilitated degradation of ciprofloxacin. Increasing zerovalent copper and H2 O2 concentrations increased ciprofloxacin removal. Degradation products of ciprofloxacin were analyzed to propose degradation pathways. Degradation of ciprofloxacin was found to result into the formation of acetate. Abstract: Ciprofloxacin (CIP), an important class of antibiotics is greatly used and discharged into aquatic environment which causes severe environmental issues. In this study, nano-scaled, stable, and highly reactive zerovalent copper (Cu°) was synthesized for the treatment of ciprofloxacin (CIP) in aqueous solution. The Cu° is an important material due to its high reduction potential and thus significantly degrade emerging organic pollutants. Besides, the Cu° synthesized in this study showed good surface area (i.e., 16.89 m 2 /g) and caused 63 % removal of CIP at 105 min under the conditions of [Cu°]0 = 0.5 g/L and [CIP]0 = 10 ppm. However, when H2 O2 was used with Cu°, the removal of CIP was promoted from 65 to 85 % at 105 min using [Cu°]0 = 0.5 g/L, [CIP]0 = 10 ppm, and [H2 O2 ]0 = 40 ppm, . CIP removal by Cu°/H2 O2 was due to ● OH that showed high reactivity, i.e., 3.95 × 10 9 (M s) –1 towards CIP. The use of high [H2 O2 ]0 and [Cu°]0 but lower [CIP]0 promoted the removal of CIP. The change in pH, addition of inorganic ions, and use of ● OH scavengers also influenced the removal of CIP by Cu°/H2 O2 . Total organic carbon (TOC) removal of CIP was investigated and showed 78 % removal of TOC at 800 min. Degradation products (DPs) of CIP were investigated to establish degradation pathways. The Cu°/H2 O2 was found to have high potential in the removal of CIP in aqueous solution as it resulted in high TOC removal of CIP, and formation of inorganic DPs and non-toxic acetate.